2004
DOI: 10.1590/s0100-41582004000300023
|View full text |Cite
|
Sign up to set email alerts
|

Eryngium foetidum, Petroselinum crispum and Coriandrum sativum: new apiaceae hosts of Oidiopsis taurica in Brazil

Abstract: Eryngium foetidum, Petroselinum crispum e Coriandrum sativum: novas hospedeiras de Oidiopsis taurica no Brasil Relata-se a infecção natural de plantas de chicória da Amazônia (Eryngium foetidum), coentro (Coriandrum sativum) e salsa (Petroselinum crispum), cultivados em casas de vegetação e campo na Embrapa Hortaliças, Brasília, DF, por Oidiopsis taurica. A provável fonte de inóculo foram plantas doentes de pimentão (Capsicum annuum) e tomate (Lycopersicon esculentum) na casa de vegetação e pimentão no campo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…These characteristics are similar to those reported by Salmon [22], Mosquera et al [23] and Glawe [24]. The conidia presented the following dimensions: 70 µm long × 18 µm wide for the lanceolate form and 65 µm long × 18 µm wide for the cylindrical form, similar to measures previously reported for L. taurica [25,26]. In the present study, no sexual spores (cleistothecia) were observed on infected leaves, as also reported by Jones et al [27] and Abdel-Azeem and Abdel-Moneim [28] who did not observe these structures.…”
Section: Identification Of the Causal Agent Of Powdery Mildew On Jala...supporting
confidence: 90%
“…These characteristics are similar to those reported by Salmon [22], Mosquera et al [23] and Glawe [24]. The conidia presented the following dimensions: 70 µm long × 18 µm wide for the lanceolate form and 65 µm long × 18 µm wide for the cylindrical form, similar to measures previously reported for L. taurica [25,26]. In the present study, no sexual spores (cleistothecia) were observed on infected leaves, as also reported by Jones et al [27] and Abdel-Azeem and Abdel-Moneim [28] who did not observe these structures.…”
Section: Identification Of the Causal Agent Of Powdery Mildew On Jala...supporting
confidence: 90%